Abundance and distribution pattern of macroinvertebrates at Watu Lumbung Beach, Gunungkidul, Yogyakarta - Rahmawati, Yunita Fera; Putri, Rizka Apriani; Prakarsa, Tatag Bagus Putra; Edhiningtyas, Chrisshinta Iris; Hermawan, Lisa Agustina (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2024)
Macroinvertebrates are one of the bioindicators in aquatic ecosystems. The diversity and distribution patterns of functional groups of macroinvertebrate communities are assessed to determine water quality. The objective of this research was to figure out the abundance and distribution of macroinvertebrates in Watu Lumbung Beach, Gunungkidul, Yogyakarta. This study was conducted in May 2022 with the quadrat transect method using 1×1 m quadrats along Watu Lumbung Beach, Gunungkidul, Yogyakarta. Sampling was conducted at two randomly determined stations from the lowest low tide to the middle of the sea. The first station is located near Watu Lumbung reef, which has a distance of 50 m, while the second station is 250 m from the reef, so the distance between stations is 200 m. The Shannon-Weiner diversity index (H') was calculated by analyzing the data. The data obtained in this study are the results of the inventory of macroinvertebrate species at each sampling point and the number of individuals of each species. The results showed the abundance of macroinvertebrates on Watu Lumbung beach found as many as 16 species belonging to 13 families and classified into nine classes (Polychaeta, Malacostraca, Anthozoa, Echinoidea, Ophiuridae, Gastropoda, Polyplacophora, Pilidiophora and Demospongia). The family Ophiocomidae (Ophiocoma erinaceus and Ophiocoma scolopendrina) were the most abundant species at both observation stations. The diversity index is 1.94, which shows that the diversity of macroinvertebrates on Watu Lumbung Beach is categorized as moderate.